HUBUNGAN PENGETAHUAN DAN SIKAP MASYARAKAT TENTANG COVID-19 DENGAN PELAKSANAAN PROTOKOL KESEHATAN - Sadeva, Aulia; Arneliwati, Arneliwati; Nopriadi, Nopriadi (Coping: Community of Publishing in Nursing; Vol 10 No 4 (2022): Agustus 2022DO - 10.24843/coping.2022.v10.i04.p08, 2022)
COVID-19 is a new disease that can cause pneumonia and respiratory problems. The increase in COVID-19 cases that continues to occur in Indonesia has made the government make various efforts to prevent the extensive spread of COVID-19 by implementing health protocols. The implementation of the health protocols must be supported by all elements of society, consisting of community knowledge and attitudes. This study aims to determine the correlations between community knowledge and attitudes about COVID-19 with the implementation of the health protocols.  The   design of this study is a quantitative descriptive correlational study with  a cross-sectional approach.  Data was collected using a questionnaire consisting of 29 statements about the knowledge, attitudes, and implementation of the health protocols of COVID-19 to 93 respondents in RW 011, North Tangkerang, Pekanbaru using a  purposive sampling technique . Data analysis used univariate analysis and bivariate analysis with the   chi-square test.  There is a correlation between knowledge and implementation of health protocols with a p-value 0,000 < (0,05) and there is a relationship attitudes and implementation of health protocols with a p-value 0,017 < (0,05). Community knowledge and attitudes have a significant correlation with the implementation of health protocols that can be useful to prevent COVID-19.